(untitled) (Current Horticulture, 2023)
The experiment was conducted to standardize regeneration protocol from ray florets in chrysanthemum cv. Pusa Arunodaya (TQP 06). For callus induction, the highest callusing percent (82.67%) with a minimum number of days for callus initiation (10.87 days) was observed in MS medium supplemented with Kinetin (10 mg/l) + NAA (1.0 mg/l) in treatment (T3). Highest shooting percent (69.33 %) with minimum number of days for shoot initiation (6.27 days) along with maximum number of shoots per explant (5.67 shoots) in MS medium supplemented with Kinetin (5.0 mg/l) + NAA (1.0 mg/l). In shoot proliferation, the highest number of shoots after 30 days (51.67), 60 days (72.00), and 90 days (98.67) in MS medium supplemented with Kinetin (5.0 mg/l) + NAA (1.0 mg/l). The highest rooting percent (85.00%) with least days for root initiation (7.00 days) along with maximum roots per shoot (8.00) and optimum root length (5.00 cm) in MS medium supplemented with IBA (0.2 mg/l). The rooted plants were successfully acclimatized in 3-4 weeks and survived under field conditions.